Knowledge of ovarian cancer in Ibadan: community-based assessment women aged 15 years and above (2014)
"Background: Non communicable diseases are increasing in proportion in developing countries. Ovarian cancer has the highest case fatality rate among gynecological cancers but forms only 3%. Its etiology is unknown, and no cost‑effective screening program exists due to the absence of well‑defined precursor lesions. Early symptoms are vague but can be used to detect Stages I and II diseases. Documented knowledge or awareness of ovarian cancer varies between 4.4% and 15%. However, this is the first community‑based survey in Africa to determine knowledge of ovarian cancer by females. Materials and Methods: The questionnaire was semi‑structured and interviewer administered. Females aged 15 years and above were selected through a four‑stage process involving urban/semi‑urban settings, local government areas, wards, and units. We randomly selected 424 participants, equally distributed between urban and semi‑urban areas. Bivariate and linear regression analyses were done. Results: Most (83.5%) of the respondents were <40 years, married (56.1%), had secondary education (52.4%), Yoruba (92.5%), and Christian (56.1%). With good knowledge score taken as having at least 70% of required information, about 2.8% of respondents had good knowledge of ovarian cancer. Only level of education and occupation significantly affected knowledge of ovarian cancer. Conclusion: There is very poor knowledge about ovarian cancer, its risk factors, symptoms, treatment, and prognosis among females in Ibadan, strongly affected by education and occupation."